2022
DOI: 10.1038/s41392-022-01130-8
|View full text |Cite
|
Sign up to set email alerts
|

The heterogeneous immune landscape between lung adenocarcinoma and squamous carcinoma revealed by single-cell RNA sequencing

Abstract: A thorough interrogation of the immune landscape is crucial for immunotherapy strategy selection and prediction of clinical responses in non-small-cell lung cancer (NSCLC) patients. Single-cell RNA sequencing (scRNA-seq) techniques have prompted the opportunity to dissect the distinct immune signatures between lung adenocarcinoma (LUAD) and lung squamous cell carcinoma (LUSC), the two major subtypes of NSCLC. Here, we performed scRNA-seq on 72,475 immune cells from 40 samples of tumor and matched adjacent norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
69
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 57 publications
5
69
0
Order By: Relevance
“…In conclusion, T cells, CSCs and macrophages were crucial contributors to the heterogeneity in TME between LUAD and LUSC, aligning with the recent findings by Wang et al. 41 …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In conclusion, T cells, CSCs and macrophages were crucial contributors to the heterogeneity in TME between LUAD and LUSC, aligning with the recent findings by Wang et al. 41 …”
Section: Resultssupporting
confidence: 91%
“…Closer proximity and stronger interaction between CD8+ T cells were observed in LUAD, whereas LUSC featured spatial proximity among PD‐L1+ cells, CD133+ CSCs and macrophages. In conclusion, T cells, CSCs and macrophages were crucial contributors to the heterogeneity in TME between LUAD and LUSC, aligning with the recent findings by Wang et al 41 …”
Section: Resultssupporting
confidence: 91%
“…The prognostic signature established with TCGA-LUAD data, validated by external datasets in the GEO database, and the comparison of nomogram and DCA can indicate that our prognostic signature related to CRFGs has better results and greater advantages in predicting the prognosis of LUAD patients, which has some significance for clinical application. The TME occupies an important position in tumorrelated research, and the evaluation of the immune system facilitates the development of personalized immunotherapy strategies for LUAD patients [44]. It has been suggested that the ferroptosis score and cuproptosis-related gene score are important for TME cell infiltration in LUAD patients and assist in assessing the effects of immunotherapy [18,45].…”
Section: Discussionmentioning
confidence: 99%
“…The TME occupies an important position in tumor-related research, and the evaluation of the immune system facilitates the development of personalized immunotherapy strategies for LUAD patients [ 44 ]. It has been suggested that the ferroptosis score and cuproptosis-related gene score are important for TME cell infiltration in LUAD patients and assist in assessing the effects of immunotherapy [ 18 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…SCGB3A2 is predominantly expressed in the lung airway epithelial cells [ 39 , 40 ]. Previous study has demonstrated that LUAD cells with highly expressed SCGB3A2 exhibited anti-inflammatory features [ 41 ], it was not clarified whether this was related to the enhanced efficacy of immunotherapy. Furthermore, SCGB3A2 is identified as a downstream target for the homeodomain transcription factor NK2 Homeobox 1 ( NKX2-1 ) (also known as TTF1 ) [ 42 ], which is utilized as a marker for LUAD diagnosis [ 43 ].…”
Section: Discussionmentioning
confidence: 99%